New insight into structure-activity of furan-based salicylate synthase (MbtI) inhibitors as potential antitubercular agents - Laurent R. Chiarelli; Matteo Mori; Giangiacomo Beretta; Arianna Gelain; Elena Pini; Josè Camilla Sammartino; Giovanni Stelitano; Daniela Barlocco; Luca Costantino; Margherita Lapillo; Giulio Poli; Isabella Caligiuri; et al. (Taylor & Francis Group, 2019)
Starting from the analysis of the hypothetical binding mode of our previous furan-based hit (I), we successfully achieved our objective to replace the nitro moiety, leading to the disclosure of a new lead exhibiting a strong activity against MbtI. Our best candidate 1 h displayed a Ki of 8.8 µM and its antimycobacterial activity (MIC99 = 250 µM) is conceivably related to mycobactin biosynthesis inhibition. These results support the hypothesis that 5-phenylfuran-2-carboxylic derivatives are a promising class of MbtI inhibitors.